The road to victory in the UEFA Women's Champions League: A multi-level analysis of successful coaches, teams, and countries - Filho, E.; Rettig, J. (Psychology of Sport and Exercise, 2018)
Objectives: To explore coach-level, team-level, and country-level factors associated with performance in the UEFA Women's Champions League. Design: This study involved archival analysis of factual data on teams and coaches participating in the UEFA Women's Champions League (2011-12 until 2015-16). Method: Official data records were provided by UEFA. Hierarchical linear modeling analysis was used to predict performance in the UEFA Women's Champions League. Specifically, coaches' characteristics (level-1 variables), team factors (level-2 variables), and country information (level-3 variables) were tested as predictors of performance (final rank, ranging from 1 to 32). Results: Data analysis yielded a two- and three-level solution. The two-level solution was deemed more realistic and applied, and was chosen as the omnibus final model. Within the two-level solution, years coaching experience in Champions League at level-1 ( g10 = -2.90), and number of times team has won Champions League ( g01 = -7.13) and number of international players ( g02 = -1.08) at level-2, predict final performance at the UEFA Women's Champions League (i.e., negative coefficient is indicative of performance improvement). Conclusions: Our findings suggest that the quality of the team, positive cross-cultural effects from an international roster, and the experience of the coach are positively associated with performance in the UEFA Women's Champions League.